Conduit Artery Diameter During Exercise Is Enhanced After Local, but Not Remote, Ischemic Preconditioning - Cocking, Scott; Cable, N. T.; Wilson, Mathew G.; Green, Daniel J.; Thijssen, Dick H. J.; Jones, Helen (Frontiers in Physiology, 2018)
Introduction: The ability of ischaemic preconditioning (IPC) to enhance exercise capacity may be mediated through altering exercise-induced blood flow and/or vascular function. This study investigated the hypothesis that (local) IPC enhances exercise-induced blood flow responses and prevents decreases in vascular function following exercise Methods: Eighteen healthy, recreationally trained, male participants (Mean ± SD: Age 32 ± 8 years; BMI 24.2 ± 2.3; Blood pressure 122 ± 10 / 72 ± 8 mmHg; Resting HR 58 ± 9 beats·min-1) received IPC (220 mmHg; 4X5-min bilateral arms), REMOTE IPC (220 mmHg; 4X5-min bilateral legs) or SHAM (20 mmHg; 4X5-min bilateral arms) in a counterbalanced order prior to 30-minutes of submaximal (25% maximal voluntary contraction; MVC) unilateral rhythmic handgrip exercise. Brachial artery diameter and blood flow were assessed every 5-minutes throughout the 30-min submaximal exercise using high resolution ultrasonography. Pre- and post-exercise vascular function was measured using flow mediated dilation. Results: IPC resulted in enlarged brachial artery diameter during exercise [0.016 cm (0.003 to 0.03 cm), P=0.015] compared to REMOTE IPC, but blood flow during exercise was similar between conditions (P>0.05). Blood flow (L/min) increased throughout exercise (time: P<0.005), but there was no main effect of condition (P=0.29) or condition*time interaction (P=0.83). Post-exercise flow mediated dilation (FMD) was similar between conditions (P>0.05). Conclusion: Our data show that local (but not remote) IPC, performed as a strategy prior to exercise, enhanced exercise-induced conduit artery diameter dilation, but these changes do not translate into increased blood flow during exercise nor impact post-exercise vascular function.